Effect of severe dietary restriction on growth and slaughter characteristics of non-selected growing rabbits - Saidj, D; Imelhayen, M; Dorbane, Z; Talaaziza, D; Chirane, MS; Korteby, HM; Moula, N; Kadi, SA (Journal of the Hellenic Veterinary Medical Society, 2023)
This work was carry out to study the effects of dietary restriction by limiting rabbit access to the feeder on fattening performance. A total of 44 weaned rabbits, of 32-35 days, were randomly divided into 2 groups, the control group (C) fed ad-libitum throughout the fattening period and the group with restricted access to the feed restriction (R). The weekly feeding program of the R group consisted of a restricted access time to the feed trough for 5 days (3h/d) and an ad libitum feed distribution for the weekend during the 5 weeks post-weaning. Two weeks before slaughter (10 to 12 weeks of age), the rabbits from the Group R were fed ad libitum. Results showed lower live weights for Group R at 10 weeks of age (R: 1084.7 g vs. C: 1510.7; p<0.05) but similar at 12 weeks of age (R: 1557.2 g vs. C: 1800.9 g; P>0.05). Different daily feed intakes throughout the fattening period and similar average daily gains (R:16.25 g/d vs. C:22.10 g/d; p>0.05). The feed intake index at the end of fattening was significantly higher in control animals (C:4.15 vs. R:3.85, p=0.001). Carcass yield was similar (C: 68.07% vs. R: 65.70%; p>0.05), peri-renal fat weight was higher in control rabbits (C: 27.17g vs. R: 13.67g; p=0.002).The results of the present study indicate the economic interest of using a feed restriction strategy that could be popularized in local rabbit farms.